Secretome analysis revealed adaptive and non‐adaptive responses of the Staphylococcus carnosus femB mutant. Issue 7 (21st January 2015) - Nega, Mulugeta; Dube, Linda; Kull, Melanie; Ziebandt, Anne‐Kathrin; Ebner, Patrick; Albrecht, Dirk; Krismer, Bernhard; Rosenstein, Ralf; Hecker, Michael; Götz, Friedrich
<x xml:space="preserve">Abstract</x> FemABX peptidyl transferases are involved in non‐ribosomal pentaglycine interpeptide bridge biosynthesis. Here, we characterized the phenotype of a Staphylococcus carnosus femB deletion mutant, which was affected in growth and showed pleiotropic effects such as enhanced methicillin sensitivity, lysostaphin resistance, cell clustering, and decreased peptidoglycan cross‐linking. However, comparative secretome analysis revealed a most striking difference in the massive secretion or release of proteins into the culture supernatant in the femB mutant than the wild type. The secreted proteins can be categorized into typical cytosolic proteins and various murein hydrolases. As the transcription of the murein hydrolase genes was up‐regulated in the mutant, they most likely represent an adaption response to the life threatening mutation. Even though the transcription of the cytosolic protein genes was unaltered, their high abundance in the supernatant of the mutant is most likely due to membrane leakage triggered by the weakened murein sacculus and enhanced autolysins.